'Taking Back Control', the UK's Constitutional Narrative and Schrodinger's Devolution. Issue 1 (30th October 2018) - Sandford, Mark; Gormley-Heenan, Cathy
Abstract: The UK's decision to leave the European Union in 2016 threatens to open up a range of territorial management issues that have long remained unexplored. Since 1999, the UK's devolution settlements have allowed divergent constitutional narratives to develop and to co-exist. This 'constructive ambiguity' has led UK territorial governance to take the form of 'Schrodinger's devolution', where Scotland, Wales and Northern Ireland have and have not experienced fundamental constitutional change. However, the technical requirements of Brexit will mandate the need for exact decisions where 'constructive ambiguity' has existed up to now. The UK's unwritten constitution, limited intergovernmental relations and a lack of shared rule mechanisms mean that these technical decisions have the potential to lead to ongoing political instability.